Synergistic Effect of Angelica gigas and Saccharin on Antiproliferative Activity in Ovcar-3 Cells - Sang Yong PARK; Yu Jin PARK; Min-Woo LEE; Ji Hye HEO; Dong-Gil KIM; Suhng Wook KIM (Korean Journal of Clinical Laboratory Science)
Many patients with ovarian epithelial cancer, which accounts for more than 90% of ovarian cancers, are resistant to chemotherapy. Accordingly, Eastern medicine, which uses natural products as medicines, has been proposed. This study quantitatively analyzed the synergistic effects of saccharin (SAC) and Angelica gigas (AG) on antiproliferative activity in Ovcar-3 cells in vitro by analyzing the changes in cell viability and colony formation when treated alone and in combination and by quantifying the combination index (CI) of the combination treatment. The SAC and AG alone decreased the viability of Ovcar-3 cells in a concentration-dependent manner, confirming their cytotoxicity against ovarian cancer cells. The combination of SAC and AG treatment decreased cell viability significantly. CI analysis confirmed that SAC and AG had a synergistic effect. In addition, the combination treatment of SAC and AG inhibited colony formation. Based on these results, the combined treatment of SAC and AG had synergistic effects on the antiproliferative activity in ovarian cancer. Therefore, the SAC and AG combined treatment is expected to be applied to treatment and nutraceuticals.